PENGARUH CEKAMAN AIR TERHADAP PRODUKSI DAN MUTU SIMPLISIA TEMPUYUNG (Sonchus arvensis L.) - MONO RAHARDJO; IRENG DARWATI (Jurnal Penelitian Tanaman Industri, 2000)
Effect of water stress on the production and quality of Sonchus arvensis L.Study on water stress in Sonchus arvensis L was conducted to improve the quality and production of leaves. Pot experiment was conducted at geen house Bogor Research Institute for Spice and Medicinal Crops from July to November 1996, with 7 kg latosol dry soil of Cimanggu Bogor per pot. Randomized block design with four replications were used. Eight treatments of water stess and casting were applied i.e. (I) 100% field capacity (FC) no casting, (2) 100% FC + casting, (3) 80% FC + casting with water stress started at 30 days alter planting (dap), (4) 60% FC + casting with water stess started at 30 dap, (5) 40% FC + casting with water stress started at 30 dap, (6) 80% FC + casting with water stress started at 50 DAP, (7) 60% FC + casting with water stress started at 50 dap, (8) 40% FC + casting with water stress started at 50 dap. Results showed that chlorophyl content leaf aea, fresh and dry weight of leaves deceased at a water stress of 60% FC strated al 30 dap the higher the water stress the lower the measurement of those parameters, but the higher the content of K and Na. The highest yield of fesh and dry leaves, respectively 53.22 and 4.58 g/plant was produced by the plants treated in 100% PC + casting. The plant treated in 40% FC started at 30 dap resulted in the highest quality of simplisia indicated by the highest content of K (8.2%) and Na (0.227%). With the treatment, K and Na conlent increased by 13.6 and 95.7% espectively and the dry weight of simplisia decreased by 62.9%.